ANALISA LITERASI KEUANGAN PADA PERILAKU PENGELOLAAN KEUANGAN PETANI KOPI DAN CENGKEH DI JAWA TENGAH - Bingawati, Bingawati; Wiguna, Graziella; Evelyn, Evelyn (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2023)
The agricultural sector plays an important role in the nation’s economy. This is because the agricultural sector provides the main job opportunities for residents in rural areas, and serves as a provider of food for the population. Besides that, agriculture is also one of the backbones of the nation’s economy and supports the country’s development. This study aims to analyze the saving behavior of coffee and clove farmers who live in Central Java, especially in Kendal, Temanggung, and Batang districts based on income levels, consumption patterns, and saving patterns owned by farmers. Data collected by a number of 102 respondents obtained through the distribution of questionnaires. The results of the analysis show that the income level, consumption patterns, and saving patterns of coffee and clove farmers in central java influence each other. This research is expected to provide benefits and information regarding the importance of financial management, especially in 3 aspects, namely consumption patterns, savings patterns and investment patterns so that farmers have good and correct household financial management.